TRAINING ON DEVELOPING CHEMISTRY EXPERIMENT PROCEDURES BASED ON THE SURROUNDING ENVIRONMENT FOR CHEMISTRY MGMP TEACHERS IN PALANGKA RAYA CITY - Fatchiyatun Ni’mah; Abudarin; Maya Erliza Enggraeni; Anggi Ristiyana Puspita Sari; Yoan Theasy; Triliyansi; Adimetha Diraja Tangkasiang; Grecya Agustin M. Marpaung (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
The Training on Developing Chemistry Experiment Procedures Based on the Surrounding Environment for Chemistry MGMP Teachers in Palangka Raya City aims to address the limited implementation of laboratory practices in schools due to inadequate facilities and the high cost of chemical reagents. The activity was conducted on June 21, 2025, involving 35 teachers, 8 lecturers, and 7 students, divided into two sessions: a material delivery session (in the lecture hall) and a practical session (in the Chemistry Education Laboratory, Faculty of Teacher Training and Education, UPR). The main objective of this community service program (PKM) is to increase teachers’ motivation to innovate in laboratory practices and to enhance their skills in designing experimental procedures using alternative materials from the surrounding environment. During the training, various examples of chemistry experiments were demonstrated, utilizing easily accessible and inexpensive materials as substitutes for reagents. The activity concluded with an independent assignment for teachers to design environmentally based experiments. Overall, this program successfully introduced practical and sustainable solutions to improve the quality and frequency of chemistry laboratory practices in schools. Evaluation results showed that the partner teachers (chemistry subject teachers) demonstrated strong motivation and were able to develop experimental designs by utilizing materials from the surrounding environment.